The roles of lifestyle, future need and customer preferences in customer’s satisfaction on Islamic Banks products and services - Mohamed Naim, Asmadi; Hamid, Mohd Liki; Wahab, Muhammad Zarunnaim (USIM, 2019)
This paper aims to address the relationship and the influence of lifestyle, future need, customer preferences toward customer’s satisfaction on Islamic banks products and services in northern region of Malaysia. This study used quantitative research method. Data were collected via questionnaires from 250 respondents from four different Islamic banks and data was analysed using SPSS v22 software. The study found that all the independent variables have positive significant relationship towards the satisfaction of Islamic banks’ services with the highest correlation is lifestyle and the lowest is future need factor. The study concluded that the lifestyle variable has the strongest influence to the dependent variable, followed by future need and customer preferences. This study provides a useful analysis to the policy makers in helping them to draft new policies and programmes relating to Islamic products and services which affects the masses. Besides, the result helps marketing team in Islamic banks to formulate strategies for future promotional activities. This paper empirically identified the relationship and the influence factors between lifestyle, future needs, customer preferences and the satisfaction among customers in using Islamic banks services.